Gender Diversity on European Banks’ Boards of Directors - Mateos de Cabo, Ruth (Journal of business ethics, 2012)
This article investigates the gender diversity of the corporate board of European Union banks. Employing a large sample of 612 European banks from 20 European countries, it identifies organizational characteristics that could be predictive of women’s presence on bank boards. We identify three factors that play a particularly important role in defining bank board gender diversity. First, the proportion of women on the board is higher for lower-risk banks. We argue that there may be some statistical discrimination behind this relation, although it could also be explained by a real risk-aversion hypothesis. Second, banks with larger boards have a higher proportion of women on their boards, which could be considered a signal of some kind of preference for homogeneity on small boards. Finally, banks that have a growth orientation are more prone to include women on their board, since they may be seen as providers of diverse external resources that are more valued by firms operating under critical circumstances.